The Effect of Rejection of Itsbat Nikah on Inheritance (Study of Judges' Legal Considerations Number: 124/Pdt.G/2023/MS.Bna): Pengaruh Penolakan Itsbat Nikah Pada Kewarisan (Studi Terhadap Pertimbangan Hukum Hakim Nomor: 124/Pdt.G/2023/MS.Bna) - Najla, Siti; Abubakar, Ali; Sri Wahyuni, Yenny (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2024)
This research aims to explain judges' legal considerations from the perspective of procedural and substantive justice. This is because the decision 124/Pdt.G/2023/MS.Bna, which was a case where the application for a marriage registration was rejected and caused problems with the purpose of the marriage ceremony, thus affecting the position of the parties before and after the decision. In this research the author used qualitative research methods and a normative juridical approach, namely by examining the judge's decisions (content analysis). The judge's legal considerations are analyzed using the theory of justice (procedural and substantive) and compared with several other decisions. The results of the research show that the decision of the Banda Aceh Syar'iyah Court which was based on the provisions of the Compilation of Islamic Law resulted in everyone having the right to become heirs except the applicant, whereas if it was based on the provisions of fiqh the applicant had the right to become an heir because the applicant's marriage was valid in harmony and according to the requirements of Islamic law. . In considering decision 124/Pdt.G/2023/MS.Bna the judge sided with the nature of procedural justice only and ignored substantive justice, resulting in formal justice which was only guided by the law. If the judge uses extra-legal considerations and substantive justice, the itsbat application is very worthy of being accepted.